The solitary wasp genus Piyuma Pate, 1944 (Hymenoptera: Crabronidae: Crabroninae) in India, with description of a new species. (3rd July 2022) - Saini, Varun; Dey, Debjani
ABSTRACT: The genus Piyuma Pate from India is reviewed, and a new species, Piyuma chapraensis (Bihar: Chapra), is described and illustrated. Furthermore, two subspecies of P. prosopoides, viz., makilingi and iwatai are redescribed with illustrations. A checklist is provided for all Piyuma species reported from the Indian subcontinent. http://www.zoobank.org/urn:lsid:zoobank.org:act:91AD2C75-AAC0-4B92-AFA4-6D59ECBA7421